Shopping centers in the context of urban communication: The case of elazig - Basgun, Ferda (Nova Science Publishers Inc., 2025)
While shopping centers are an important and indispensable element of modern urban life, they are increasingly important in urban communication. Shopping centers are preferred for shopping purposes. Apart from the meaning of its name, shopping centers serve people with minimized urban logic by incorporating reduced-scale indoor physical and social areas such as social interaction, cultural activities, and recreational areas in a city in a modern urban structure. Therefore, shopping centers are becoming increasingly important structures that improve the quality of life in cities and contribute to urban transformation. These centers can reflect the diversity of urban life by bringing together people from different socioeconomic groups. In addition to meeting the needs of city dwellers, shopping centers also contribute to urban communication by providing opportunities to come together and interact. Other services and infrastructure that develop around shopping malls also have a modernizing effect on the urban fabric and improve urban communication and access. However, shopping centers have both negative and positive aspects of urban communication. In particular, the effects of large shopping centers on the environment, traffic density, and replacing traditional marketplaces and streets with shopping centers can lead to changes in urban fabric, identity, and communication. In this chapter, which examined shopping centers in the context of urban communication through the example of the Elazig Park 23 Shopping Center, a qualitative method based on a hermeneutic approach was preferred to read and evaluate shopping centers, which minimizes reflections of the layered and complex structure of the city, with a holistic perspective in terms of urban communication. The conceptual structure of "narrative," which forms the basis of the hermeneutic approach and makes relationships visible, has been used to understand shopping centers in urban communication. In this chapter, the layered and complex structure of shopping centers, as in cities, has been studied through the example of the Elazig Park 23 Shopping Center. In this context, this chapter contributes to the literature by drawing attention to shopping centers in the context of urban communication. © 2025 by Nova Science Publishers, Inc.
Keywords: City; Shopping centers; Urban communication